STRATEGI PEMENUHAN KEBUTUHAN INFORMASI PERTANIAN MELALUI PEMANFAATAN CYBER EXTENSION DI PROPINSI LAMPUNG - Dame Trully Gultom (Sosiohumaniora, 2017)
Production of some vegetables in  Lampung Province showed to decline in  the past five years, due to agricultural information technology does not distribute evenly, while the cyber extension could be used to search the agricultural information. The aims of study are (1)  Analyze the factors that influence the horticulture farmers communication behavior to fulfill the need of agricultural information, (2) Formulating the strategy of fulfillment need of agriculture information through the use of cyber extension.  Research design was Sequential Explanatory Design (Mixed Methods). The research was conducted in 16 villages in West Lampung District and Tanggamus District, from October 2014 to January 2015. Respondent samples were taken with sampling quota as many as 180 farmers. The data used were primary and secondary data.  Data analyzed by descriptive analyzed  and inferential analyzed by The Structural Equation Model  (SEM). The results of the study concluded that farmers communication behavior is positively influenced by the individual characteristics, the environmental factors, the potential of cyber extension information source and the potential of conventional information source.  The need fulfillment of  agricultural information  is influenced  by the farmers communication behavior.